A Dual‐Bioresponsive Drug‐Delivery Depot for Combination of Epigenetic Modulation and Immune Checkpoint Blockade. Issue 17 (11th March 2019) - Ruan, Huitong; Hu, Quanyin; Wen, Di; Chen, Qian; Chen, Guojun; Lu, Yifei; Wang, Jinqiang; Cheng, Hao; Lu, Weiyue; Gu, Zhen
Abstract: Patients with advanced melanoma that is of low tumor‐associated antigen (TAA) expression often respond poorly to PD‐1/PD‐L1 blockade therapy. Epigenetic modulators, such as hypomethylation agents (HMAs), can enhance the antitumor immune response by inducing TAA expression. Here, a dual bioresponsive gel depot that can respond to the acidic pH and reactive oxygen species (ROS) within the tumor microenvironment (TME) for codelivery of anti‐PD1 antibody (aPD1) and Zebularine (Zeb), an HMA, is engineered. aPD1 is first loaded into pH‐sensitive calcium carbonate nanoparticles (CaCO3 NPs), which are then encapsulated in the ROS‐responsive hydrogel together with Zeb (Zeb‐aPD1‐NPs‐Gel). It is demonstrated that this combination therapy increases the immunogenicity of cancer cells, and also plays roles in reversing immunosuppressive TME, which contributes to inhibiting the tumor growth and prolonging the survival time of B16F10‐melanoma‐bearing mice. Abstract : A dual bioresponsive drug delivery depot is engineered, which can respond to the acidic pH and reactive oxygen species within the tumor microenvironment (TME), for codelivery of anti‐PD1 antibody and Zebularine, an epigenetic modulator. It is demonstrated that this combination therapy increases the immunogenicity of cancer cells, reverses immunosuppressive TME, and enhances the antitumor immune response.